THE PLACE OF CRAFTSMANSHIP SHOPS IN THE MARKET INFRASTRUCTURE IN THE KHIVA KHANATE (TAMADDUN NURI JURNALI, 2025)
This article discusses the state of handicrafts in the Khiva Khanate in the 19th century, the activities of artisans, and provides information about workshops and shops. It also addresses the types of handicrafts, the specific neighborhoods of artisans, the sale of goods necessary for internal and external trade in markets, as well as issues related to the social life of the people and the types of goods needed for their daily needs.